Coalition Against Major Diseases/European Medicines Agency biomarker qualification of hippocampal volume for enrichment of clinical trials in predementia stages of Alzheimer's disease. Issue 4 (1st July 2014) - Hill, Derek L.G.; Schwarz, Adam J.; Isaac, Maria; Pani, Luca; Vamvakas, Spiros; Hemmings, Robert; Carrillo, Maria C.; Yu, Peng; Sun, Jia; Beckett, Laurel; Boccardi, Marina; Brewer, James; et al.
Abstract: Background: Regulatory qualification of a biomarker for a defined context of use provides scientifically robust assurances to sponsors and regulators that accelerate appropriate adoption of biomarkers into drug development. Methods: The Coalition Against Major Diseases submitted a dossier to the Scientific Advice Working Party of the European Medicines Agency requesting a qualification opinion on the use of hippocampal volume as a biomarker for enriching clinical trials in subjects with mild cognitive impairment, incorporating a scientific rationale, a literature review and a de novo analysis of Alzheimer's Disease Neuroimaging Initiative data. Results: The literature review and de novo analysis were consistent with the proposed context of use, and the Committee for Medicinal Products for Human Use released an opinion in November 2011. Conclusions: We summarize the scientific rationale and the data that supported the first qualification of an imaging biomarker by the European Medicines Agency.